Therapeutic Application of Pluripotent Stem Cells: Challenges and Risks - Martin, Ulrich (Frontiers in Medicine, 2017)
Stem cell based therapies are considered to be promising and innovative but complex approaches. Induced pluripotent stem cells (iPSCs) combine the advantages of adult stem cells with the hitherto unique characteristics of embryonic stem cells. Major progress has already been achieved with regard to reprogramming technology, targeted genome editing and scalable expansion and differentiation of iPSCs, in some cases yielding highly enriched preparations of well-defined cell lineages at clinically required dimensions. It is noteworthy, however, that for many applications critical requirements such as the targeted specification into distinct cellular subpopulations and a proper cell maturation remain to be achieved. Moreover, current hurdles such as low survival rates and insufficient functional integration of cellular transplants remain to be overcome. Nevertheless, iPSC technologies obviously have come of age and matured to a stage where various clinical applications of iPSC-based cellular therapies have been initiated and are conducted.